Micropatterned Protein for Cell Adhesion through Phototriggered Charge Change in a Polyvinylpyrrolidone Hydrogel. (12th May 2017) - Ming, Zunzhen; Ruan, Xing; Bao, Chunyan; Lin, Qiuning; Yang, Yi; Zhu, Linyong
Abstract : Regulated immobilization of proteins on hydrogels allows for the creation of highly controlled microenvironments to meet the special requirements of cell biology and tissue engineering devices. Light is an ideal stimulus to regulate immobilization because it can be controlled in time, space, and intensity. Here, a photoresponsive hydrogel that enables the patterning of proteins by a combination of electrostatic adsorption and photoregulated charge change on a hydrogel is developed. It is based on a photosensitive cationic monomer (CLA ), a coumarin caged lysine betaine zwitterion, incorporated into a polyvinylpyrrolidone (PVP ) hydrogel, which can controllably change the charge from an adhesive positive state to an anti‐adhesive zwitterion state upon irradiation at 365 nm. With this strategy, the immobilization of proteins is regulated and cell adhesion is programmed on hydrogels on demand. This approach should open up new avenues for hydrogels in biomedical applications. Abstract : Using two bio‐orthogonal interactions, electrostatic adsorption and photorelease, regulated protein and cell adhesion is accomplished on hydrogels. Combining light manipulation and mild electrostatic interactions allows the temporal, spatial, and dosage control of protein and cell adhesion to the hydrogel, which should allow for the use of hydrogels in biomedical applications.